Basalt fiber toughened low-expansion glass-based composite material and preparation method thereof
By introducing basalt fibers into glass-based composite materials and adopting specific preparation methods, the problem of insufficient strength and expansion coefficient of existing materials is solved, and high-strength, low-expansion and low-porosity composite materials are realized, suitable for aerospace fields .
Patent Information
- Application Number
- CN202411579144.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-18
AI Technical Summary
The existing glass-based composite materials cannot meet the strength requirements in the aerospace field, and their expansion coefficient is large, which cannot quickly adapt to temperature changes, and high porosity affects strength and stability.
A low-expanded glass-based composite material with basalt fiber toughening is prepared through specific ratios and preparation methods, including ball milling and ultrasonic foaming defoaming.
The flexural strength of the glass-based composite material that achieves basalt fiber toughening reaches 107.85MPa, the density is not greater than 2.3g/cm3, and the minimum average linear expansion coefficient is 0.9×10-6/K, which significantly improves the mechanical properties and stability of the material. sex.
Smart Images

Figure CN119461861A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to a basalt fiber toughened low expansion glass-based composite material and a preparation method thereof. Background Art
[0002] With the rapid development of the aerospace field, higher quality requirements are placed on precision components used in extreme environments. The structural materials of precision components need to simultaneously meet the requirements of light weight, low and adjustable thermal expansion coefficient, high strength, high density, and easy processing.
[0003] Currently, composite materials are considered to be an effective way to achieve the above-mentioned properties. However, existing glass-based composite materials cannot meet the strength requirements of the aerospace field, and their expansion system is large and cannot quickly adapt to temperature changes. The large number of pores affects their own strength and stability.
[0004] Basalt short fiber has excellent high tensile strength (2500MPa), high working temperature (800-1000℃), low density (2.56g / cm 3 ) and good chemical stability, and is often used as a toughening and reinforcing material. However, the existing composite material system reinforced with basalt fiber is usually used in the field of concrete, and the fiber length is long (millimeter level), which is difficult to be used in fields with complex environments such as aerospace, and basalt short fibers (micrometer level) are prone to agglomeration in water, making it difficult to prepare uniformly dispersed composite material slurry. In response to the above technical phenomena, the inventor invented a new composite material toughened with basalt fiber and a preparation method thereof. Summary of the invention
[0005] The object of the present invention is to provide a basalt fiber toughened low expansion glass-based composite material and a preparation method thereof, so as to obtain a composite material with high strength, low expansion coefficient and low porosity.
[0006] The present invention provides a basalt fiber toughened low expansion glass-based composite material, which adopts the following technical solution:
[0007] A basalt fiber toughened low expansion glass-based composite material comprises the following components in percentage by weight: 30wt%-48wt% of beta-eucryptite, 0.2wt%-6wt% of basalt fiber and 51.5wt%-67.5wt% of high borosilicate glass powder.
[0008] Preferably, the diameter of the basalt fiber is 5-10 μm;
[0009] The aspect ratio of the basalt fiber is 15-30.
[0010] Preferably, the high borosilicate glass powder includes SiO2, B2O3, Al2O3, Na2O, and ZnO;
[0011] The particle size of the high borosilicate glass powder is 0.2-0.5 μm.
[0012] Preferably, the particle size of the β-eucryptite is 0.2-0.9 μm.
[0013] The present invention also provides a method for preparing a basalt fiber-reinforced low-expansion glass-based composite material, using the above-mentioned basalt fiber-reinforced low-expansion glass-based composite material, comprising the following preparation steps:
[0014] S1. Take β-eucryptite, basalt fiber and high borosilicate glass powder according to the proportions for use;
[0015] S2, taking tetraethyl orthosilicate and aluminum isopropoxide respectively, mixing them to prepare an alkaline aqueous solution, placing the basalt fiber in step S1 in the alkaline aqueous solution, heating and stirring, and preparing a basalt fiber premix;
[0016] S3, adding the β-eucryptite and high borosilicate glass powder in step S1 and the basalt premix prepared in step S2 to a ball mill, adding zirconium oxide balls to the ball mill, setting the speed and time of the ball mill to obtain a uniform slurry, and ultrasonically degassing the uniform slurry to obtain a ternary composite slurry;
[0017] S4, placing the ternary composite slurry obtained in step S3 in a prefabricated dry gypsum mold, leaving it to solidify for 10-16 hours, and then demolding it to obtain a composite green body;
[0018] S5, drying the composite material green body obtained in step S4 to obtain a composite material green body;
[0019] S6, sintering the composite material blank obtained in step S5 to obtain a basalt fiber-reinforced glass-based composite material.
[0020] Preferably, in step S2, the concentration of tetraethyl orthosilicate is 2wt%-10wt%, and the concentration of aluminum isopropoxide is 1wt%-5wt%;
[0021] The heating temperature in step S2 is 30-55° C., and the stirring is performed for 30-60 minutes by means of magnetic stirring.
[0022] Preferably, in step S3, the ratio of the amount of zirconia balls to the amount of material in the ball mill is 2:1, the diameter of the zirconia balls is 3-5 mm, the rotation speed of the ball mill is 150-250 rpm, and the time is 1-2 h.
[0023] Preferably, the solid content of the uniform slurry in step S3 is 50-62.5%;
[0024] The uniform slurry in step S3 is subjected to ultrasonic defoaming under vacuum conditions, with a vacuum degree of -0.01 to -0.03 MPa, an ultrasonic power of 40 to 50 W, and an ultrasonic time of 10 to 15 min.
[0025] Preferably, the drying process in step S5 comprises: drying the composite green body at a temperature of 21-25° C. and a humidity of 60-80% for 1-3 days, and then drying at a temperature of 50-60° C. for 12-36 hours.
[0026] Preferably, the sintering process in step S6 includes: placing the composite body in a muffle furnace, applying a pressure of 15-50 MPa to the sample by mechanical pressure, setting the temperature of the muffle furnace to 860-900°C, the vacuum degree to -0.8 to -0.9 MPa, sintering for 3-7 hours, cooling to 560-580°C, keeping the temperature for 1-2 hours, and then naturally cooling to 21-26°C;
[0027] The heating rate of the muffle furnace is 3-6℃ / min;
[0028] The cooling rate of the muffle furnace is 3-8℃ / min.
[0029] In summary, the present invention includes the following beneficial technical effects:
[0030] 1. The present invention utilizes high borosilicate glass material with low density, low thermal expansion coefficient, high chemical stability and good processability as the matrix material of lightweight and high-performance composite parts, selects high mechanical performance basalt fiber with similar chemical composition to the glass matrix, and utilizes the advantages of high tensile strength, low density, low thermal expansion coefficient, high working temperature and the like of basalt fiber to achieve toughening and reinforcement of the brittle glass matrix, so that the flexural strength of the glass-based composite material toughened by basalt fiber reaches 107.85Mpa, and the mechanical properties of the glass-based composite material are improved. Under the condition of ensuring a certain mechanical strength, the density of the glass-based composite material toughened by basalt fiber is not more than 2.3g / cm 3 The introduction of β-eucryptite with negative thermal expansion coefficient reduces the thermal expansion coefficient of basalt fiber-reinforced glass-based composites, making the average linear expansion coefficient of basalt fiber-reinforced glass-based composites as low as 0.9×10 -6 / K.
[0031] 2. The preparation method of the basalt fiber-reinforced glass-based composite material of the present invention includes modifying the surface of the basalt fiber to improve the uniform and stable dispersion of the basalt fiber in the three-phase composite material, and improving the wettability of the interface between the basalt fiber and the glass matrix, and further improving the density and strength of the composite material through vacuum pressure sintering, and reducing the porosity during the molding process. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a scanning electron microscope photograph of the composite material blank prepared in Example 1 of the present invention.
[0033] Figure 2 This is a thermal expansion coefficient diagram of the basalt fiber-toughened glass-based composite material prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0034] The following is combined with the embodiments and the attached Figure 1-2 The present invention is described in further detail.
[0035] Example 1
[0036] A basalt fiber toughened low expansion glass-based composite material, and a preparation method thereof:
[0037] 1) Take 0.15g of basalt fiber with a diameter of 10μm and an aspect ratio of 15, 21.40g of high borosilicate glass powder with a particle size of 0.5μm and 10.15g of β-eucryptite with a particle size of 0.9μm, take tetraethyl orthosilicate and aluminum isopropoxide, mix them to make 31.7ml of alkaline aqueous solution (the pH of the alkaline aqueous solution is 9, the concentration of tetraethyl orthosilicate is 2wt%, and the concentration of aluminum isopropoxide is 5wt%), place the basalt fiber in the alkaline aqueous solution, heat to 45°C, and stir magnetically for 60min to obtain a basalt fiber premix;
[0038] 2) Add the β-eucryptite and high borosilicate glass powder in step 1) and the basalt premix prepared in step S2 to a ball mill, and add 63.4 g of zirconia balls with a diameter of 3 mm to the ball mill, set the ball mill speed to 150 rpm, and the time to 1 hour to obtain a uniform slurry with a solid content of 50%. The uniform slurry is subjected to ultrasonic defoaming, that is, the uniform slurry is placed in an ultrasonic instrument in a vacuum box at room temperature, the vacuum degree is set to -0.01 MPa, the ultrasonic power is 50 W, and the ultrasonic time is 10 min to remove bubbles to obtain a ternary composite slurry;
[0039] 3) slowly pouring the ternary composite slurry obtained in step 2) into a prefabricated dry gypsum mold, standing and curing for 16 hours, and then demolding to obtain a composite green body;
[0040] 4) Drying the composite green body obtained in step 3), that is, drying the composite green body at a temperature of 21-25° C. and a humidity of 60% for 1 day, and then placing the composite green body in an oven, setting the oven temperature to 60° C. and drying for 12 hours to obtain a composite green body;
[0041] 5) Sintering the composite material body obtained by step 4) is performed by placing the composite material body in a muffle furnace, applying a pressure of 15 MPa to the top of the composite material body by mechanical pressure, evacuating to a vacuum degree of -0.8 MPa, first heating to 900 ° C at a heating rate of 6 ° C / min, keeping warm for 3 hours in a vacuum environment, then reducing the temperature to 580 ° C at a rate of 8 ° C / min, keeping warm for 1 hour, and finally naturally cooling to room temperature with the furnace to obtain a basalt fiber toughened glass-based composite material.
[0042] The high borosilicate glass powder includes SiO2, B2O3, Al2O3, Na2O, and ZnO.
[0043] Reference Figure 1 The flexural strength of the basalt fiber-reinforced glass-based composite material obtained in Example 1 is 99.56 Mpa. Figure 1 The SEM image of the cross section of the composite body prepared in this example shows that the matrix powder inside the unsintered body is densely packed, and the basalt fibers are interwoven and randomly distributed in the matrix in an irregular three-dimensional manner. The body as a whole exhibits excellent uniformity and density. The density of the composite material in this example is 2.29 g / cm 3 The average linear expansion coefficient is 1.26×10 -6 / K.
[0044] Example 2
[0045] A basalt fiber toughened low expansion glass-based composite material, and a preparation method thereof:
[0046] 1) Take 0.063g of basalt fiber with a diameter of 10μm and an aspect ratio of 20, 16.42g of high borosilicate glass powder with a particle size of 0.5μm and 10.15g of β-eucryptite with a particle size of 0.5μm, take tetraethyl orthosilicate and isopropanol, mix them to make 31.7ml of alkaline aqueous solution (the pH of the alkaline aqueous solution is 9, the concentration of tetraethyl orthosilicate is 10wt%, and the concentration of isopropanol is 1wt%), take basalt fiber and place it in the alkaline aqueous solution, heat it to 30°C, and stir it magnetically for 60min to obtain a basalt fiber premix;
[0047] 2) Add the β-eucryptite and high borosilicate glass powder in step 1) and the basalt premix prepared in step S2 to a ball mill, add 63.4 g of zirconia balls with a diameter of 3 mm to the ball mill, set the ball mill speed to 250 rpm, and the time to 1 h to obtain a uniform slurry with a solid content of 50%. The uniform slurry is subjected to ultrasonic defoaming, that is, the uniform slurry is placed in an ultrasonic instrument in a vacuum box at room temperature, the vacuum degree is set to -0.02 MPa, the ultrasonic power is 40 W, and the ultrasonic time is 15 min to remove bubbles to obtain a ternary composite slurry;
[0048] 3) slowly pouring the ternary composite slurry obtained in step 2) into a prefabricated dry gypsum mold, standing and curing for 10 hours, and then demolding to obtain a composite green body;
[0049] 4) Drying the composite green body obtained in step 3), that is, drying the composite green body at a temperature of 21-25° C. and a humidity of 80% for 3 days, and then placing the composite green body in an oven, setting the oven temperature to 60° C. and drying time to 24 hours to obtain a composite green body;
[0050] 5) Sintering the composite material body obtained by step 4) is performed by placing the composite material body in a muffle furnace, applying a pressure of 50 MPa to the top of the composite material body by mechanical pressure, evacuating to a vacuum degree of -0.9 MPa, first increasing the temperature to 860 ° C at a heating rate of 5 ° C / min, keeping the temperature in a vacuum environment for 7 hours, then decreasing the temperature to 580 ° C at a rate of 3 ° C / min, keeping the temperature for 1 hour, and finally naturally cooling to room temperature with the furnace to obtain a basalt fiber toughened glass-based composite material.
[0051] The high borosilicate glass powder includes SiO2, B2O3, Al2O3, Na2O, and ZnO.
[0052] Reference Figure 2 , Figure 2 : is the linear expansion coefficient diagram of the basalt fiber toughened glass-based composite material prepared in Example 2. The flexural strength of the basalt fiber toughened glass-based composite material prepared in Example 2 is 107.85 MPa and the density is 2.22 g / cm 3 The average linear expansion coefficient is 0.9×10 -6 / K.
[0053] Example 3
[0054] A basalt fiber toughened low expansion glass-based composite material, and a preparation method thereof:
[0055] 1) Take 0.3g of basalt fiber with a diameter of 10μm and an aspect ratio of 25, 17.13g of high borosilicate glass powder with a particle size of 0.2μm and 14.27g of β-eucryptite with a particle size of 0.2μm, take tetraethyl orthosilicate and isopropanol, mix them to make 31.7ml of alkaline aqueous solution (the pH of the alkaline aqueous solution is 9, the concentration of tetraethyl orthosilicate is 8wt%, and the concentration of isopropanol is 2wt%), take basalt fiber and place it in the alkaline aqueous solution, heat it to 55°C, and stir it magnetically for 30min to obtain a basalt fiber premix;
[0056] 2) Add the β-eucryptite and high borosilicate glass powder in step 1) and the basalt premix prepared in step S2 to a ball mill, and add 63.4 g of zirconia balls with a diameter of 5 mm to the ball mill, set the ball mill speed to 200 rpm, and the time to 2 h to obtain a uniform slurry with a solid content of 62.5%. The uniform slurry is subjected to ultrasonic defoaming, that is, the uniform slurry is placed in an ultrasonic instrument in a vacuum box at room temperature, the vacuum degree is set to -0.03 MPa, the ultrasonic power is 45 W, and the ultrasonic time is 12 min to remove bubbles to obtain a ternary composite slurry;
[0057] 3) slowly pouring the ternary composite slurry obtained in step 2) into a prefabricated dry gypsum mold, standing and curing for 12 hours, and then demolding to obtain a composite green body;
[0058] 4) Drying the composite green body obtained in step 3), that is, drying the composite green body at a temperature of 21-25° C. and a humidity of 60% for 2 days, and then placing the composite green body in an oven, setting the oven temperature to 50° C. and the drying time to 36 hours to obtain a composite green body;
[0059] 5) Sintering the composite material body obtained by step 4) is performed by placing the composite material body in a muffle furnace, applying a pressure of 35 MPa to the top of the composite material body by mechanical pressure, evacuating to a vacuum degree of -0.9 MPa, first increasing the temperature to 860 ° C at a heating rate of 3 ° C / min, keeping it warm for 5 hours in a vacuum environment, then decreasing the temperature to 580 ° C at a rate of 5 ° C / min, keeping it warm for 2 hours, and finally cooling it naturally to room temperature with the furnace to obtain a basalt fiber toughened glass-based composite material.
[0060] The high borosilicate glass powder includes SiO2, B2O3, Al2O3, Na2O, and ZnO.
[0061] The basalt fiber-reinforced glass-based composite material obtained in Example 3 has a flexural strength of 104.85 MPa and a density of 2.28 g / cm 3 .
[0062] Example 4
[0063] A basalt fiber toughened low expansion glass-based composite material, and a preparation method thereof:
[0064] 1) Take 1.9g of basalt fiber with a diameter of 10μm and an aspect ratio of 30, 16.33g of high borosilicate glass powder with a particle size of 0.2μm and 13.47g of β-eucryptite with a particle size of 0.9μm, take tetraethyl orthosilicate and isopropanol, mix them to make 31.7ml of alkaline aqueous solution (the pH of the alkaline aqueous solution is 8, the concentration of tetraethyl orthosilicate is 8wt%, and the concentration of isopropanol is 2wt%), place the basalt fiber in the alkaline aqueous solution, heat to 45°C, and stir magnetically for 50min to obtain a basalt fiber premix;
[0065] 2) Add the β-eucryptite and high borosilicate glass powder in step 1) and the basalt premix prepared in step S2 to a ball mill, and add 63.4 g of zirconia balls with a diameter of 5 mm to the ball mill, set the ball mill speed to 250 rpm, and the time to 1.5 h to obtain a uniform slurry with a solid content of 62.5%. The uniform slurry is subjected to ultrasonic defoaming, that is, the uniform slurry is placed in an ultrasonic instrument in a vacuum box at room temperature, the vacuum degree is set to -0.03 MPa, the ultrasonic power is 50 W, and the ultrasonic time is 15 min to remove bubbles to obtain a ternary composite slurry;
[0066] 3) slowly pouring the ternary composite slurry obtained in step 2) into a prefabricated dry gypsum mold, standing and curing for 12 hours, and then demolding to obtain a composite green body;
[0067] 4) Drying the composite green body obtained in step 3), that is, drying the composite green body at a temperature of 21-25° C. and a humidity of 80% for 3 days, and then placing the composite green body in an oven, setting the oven temperature to 50° C. and the drying time to 24 hours to obtain a composite green body;
[0068] 5) Sintering the composite material body obtained by step 4) is performed by placing the composite material body in a muffle furnace, applying a pressure of 15 MPa to the top of the composite material body by mechanical pressure, evacuating to a vacuum degree of -0.8 MPa, first increasing the temperature to 860°C at a heating rate of 4°C / min, keeping the temperature in a vacuum environment for 6 hours, then decreasing the temperature to 580°C at a rate of 6°C / min, keeping the temperature for 2 hours, and finally naturally cooling to room temperature with the furnace to obtain a basalt fiber-reinforced glass-based composite material.
[0069] The high borosilicate glass powder includes SiO2, B2O3, Al2O3, Na2O, and ZnO.
[0070] The basalt fiber-reinforced glass-based composite material obtained in Example 4 has a flexural strength of 92.3 MPa and a density of 2.30 g / cm 3 .
[0071] Comparative Example 1
[0072] A basalt fiber toughened low expansion glass-based composite material, and a preparation method thereof:
[0073] 1) Take 1.9g of basalt fiber with a diameter of 10μm and an aspect ratio of 30, 16.33g of high borosilicate glass powder with a particle size of 0.2μm and 13.47g of β-eucryptite with a particle size of 0.9μm, take tetraethyl orthosilicate and isopropanol, mix them to make 31.7ml of alkaline aqueous solution (the pH of the alkaline aqueous solution is 8, the concentration of tetraethyl orthosilicate is 8wt%, and the concentration of isopropanol is 2wt%), place the basalt fiber in the alkaline aqueous solution, heat to 45°C, and stir magnetically for 50min to obtain a basalt fiber premix;
[0074] 2) Add the β-eucryptite and high borosilicate glass powder in step 1) and the basalt premix prepared in step S2 to a ball mill, add 63.4 g of zirconia balls with a diameter of 5 mm to the ball mill, set the ball mill speed to 250 rpm, and the time to 1.5 h to prepare a ternary composite slurry, the solid content of the ternary composite slurry is 62.5%;
[0075] 3) slowly pouring the ternary composite slurry obtained in step 2) into a prefabricated dry gypsum mold, standing and curing for 12 hours, and then demolding to obtain a composite green body;
[0076] 4) Drying the composite green body obtained in step 3), that is, drying the composite green body at a temperature of 21-25° C. and a humidity of 80% for 3 days, and then placing the composite green body in an oven, setting the oven temperature to 50° C. and the drying time to 24 hours to obtain a composite green body;
[0077] 5) Sintering the composite material body obtained by step 4) is performed by placing the composite material body in a muffle furnace, applying a pressure of 15 MPa to the top of the composite material body by mechanical pressure, evacuating to a vacuum degree of -0.8 MPa, first increasing the temperature to 860°C at a heating rate of 4°C / min, keeping the temperature in a vacuum environment for 6 hours, then decreasing the temperature to 580°C at a rate of 6°C / min, keeping the temperature for 2 hours, and finally naturally cooling to room temperature with the furnace to obtain a basalt fiber-reinforced glass-based composite material.
[0078] The high borosilicate glass powder includes SiO2, B2O3, Al2O3, Na2O, and ZnO.
[0079] The basalt fiber toughened glass-based composite material obtained in this comparative example 1 has a flexural strength of 78.39 MPa and a density of 2.31 g / cm 3 .
[0080] Comparative Example 2
[0081] A basalt fiber toughened low expansion glass-based composite material, and a preparation method thereof:
[0082] 1) Take 1.9g of basalt fiber with a diameter of 10μm and an aspect ratio of 30, 16.33g of borosilicate glass powder with a particle size of 0.2μm and 13.47g of β-eucryptite with a particle size of 0.9μm, take 31.7ml of aqueous solution, place the basalt fiber in the aqueous solution, heat to 45°C, and stir magnetically for 50min to obtain a basalt fiber premix;
[0083] 2) Add the β-eucryptite and high borosilicate glass powder in step 1) and the basalt premix prepared in step S2 to a ball mill, and add 63.4 g of zirconia balls with a diameter of 5 mm to the ball mill, set the ball mill speed to 250 rpm, and the time to 1.5 h to obtain a uniform slurry with a solid content of 62.5%. The uniform slurry is subjected to ultrasonic defoaming, that is, the uniform slurry is placed in an ultrasonic instrument in a vacuum box at room temperature, the vacuum degree is set to -0.03 MPa, the ultrasonic power is 50 W, and the ultrasonic time is 15 min to remove bubbles to obtain a ternary composite slurry;
[0084] 3) slowly pouring the ternary composite slurry obtained in step 2) into a prefabricated dry gypsum mold, standing and curing for 12 hours, and then demolding to obtain a composite green body;
[0085] 4) Drying the composite green body obtained in step 3), that is, drying the composite green body at a temperature of 21-25° C. and a humidity of 80% for 3 days, and then placing the composite green body in an oven, setting the oven temperature to 50° C. and the drying time to 24 hours to obtain a composite green body;
[0086] 5) Sintering the composite material body obtained by step 4) is performed by placing the composite material body in a muffle furnace, applying a pressure of 15 MPa to the top of the composite material body by mechanical pressure, evacuating to a vacuum degree of -0.8 MPa, first increasing the temperature to 860°C at a heating rate of 4°C / min, keeping the temperature in a vacuum environment for 6 hours, then decreasing the temperature to 580°C at a rate of 6°C / min, keeping the temperature for 2 hours, and finally naturally cooling to room temperature with the furnace to obtain a basalt fiber-reinforced glass-based composite material.
[0087] The high borosilicate glass powder includes SiO2, B2O3, Al2O3, Na2O, and ZnO.
[0088] The basalt fiber toughened glass-based composite material obtained in this comparative example 2 has a flexural strength of 75.37 MPa and a density of 2.30 g / cm 3 .
[0089] Comparative Example 3
[0090] A basalt fiber toughened low expansion glass-based composite material, and a preparation method thereof:
[0091] 1) Take 1.9g of basalt fiber with a diameter of 10μm and an aspect ratio of 30, 16.33g of borosilicate glass powder with a particle size of 0.2μm and 13.47g of β-eucryptite with a particle size of 0.9μm, take 31.7ml of aqueous solution, place the basalt fiber in the aqueous solution, heat to 45°C, and stir magnetically for 50min to obtain a basalt fiber premix;
[0092] 2) Add the β-eucryptite and high borosilicate glass powder in step 1) and the basalt premix prepared in step S2 to a ball mill, and add 63.4 g of zirconia balls with a diameter of 5 mm to the ball mill, set the ball mill speed to 250 rpm, and the time to 1.5 h to obtain a uniform slurry with a solid content of 62.5%. The uniform slurry is subjected to ultrasonic defoaming, that is, the uniform slurry is placed in an ultrasonic instrument in a vacuum box at room temperature, the vacuum degree is set to -0.03 MPa, the ultrasonic power is 50 W, and the ultrasonic time is 15 min to remove bubbles to obtain a ternary composite slurry;
[0093] 3) slowly pouring the ternary composite slurry obtained in step 2) into a prefabricated dry gypsum mold, standing and curing for 12 hours, and then demolding to obtain a composite green body;
[0094] 4) Drying the composite green body obtained in step 3), that is, drying the composite green body at a temperature of 21-25° C. and a humidity of 80% for 3 days, and then placing the composite green body in an oven, setting the oven temperature to 50° C. and the drying time to 24 hours to obtain a composite green body;
[0095] 5) Sintering the composite material body obtained in step 4) by placing the composite material body in a muffle furnace, evacuating to a vacuum degree of -0.8 MPa, first heating to 860°C at a heating rate of 4°C / min, keeping warm for 6 hours in a vacuum environment, then reducing the temperature to 580°C at a rate of 6°C / min, keeping warm for 2 hours, and finally naturally cooling to room temperature with the furnace to obtain a basalt fiber-reinforced glass-based composite material.
[0096] The high borosilicate glass powder includes SiO2, B2O3, Al2O3, Na2O, and ZnO.
[0097] The basalt fiber toughened glass-based composite material obtained in this comparative example 2 has a flexural strength of 72.33 MPa and a density of 2.33 g / cm 3 .
[0098] Comparative Example 4
[0099] A basalt fiber-reinforced low-expansion glass-based composite material, which is different from Example 4 in that the heating rate of the muffle furnace in step 5) is 8° C. / min, and the remaining steps are the same as Example 4.
[0100] The basalt fiber toughened glass-based composite material obtained in this comparative example 4 has a flexural strength of 82.77 MPa and a density of 2.31 g / cm 3 .
[0101] Comparative Example 5
[0102] A basalt fiber-reinforced low-expansion glass-based composite material, which is different from Example 4 in that the cooling rate of the muffle furnace in step 5) is 10° C. / min, and the remaining steps are the same as Example 4.
[0103] The basalt fiber toughened glass-based composite material obtained in this comparative example 5 has a flexural strength of 82.41 MPa and a density of 2.34 g / cm 3 .
[0104] Comparative Example 6
[0105] A basalt fiber-reinforced low-expansion glass-based composite material, which is different from Example 4 in that the cooling rate of the muffle furnace in step 5) is 1.5°C / min, and the remaining steps are the same as Example 4.
[0106] The basalt fiber toughened glass-based composite material obtained in this comparative example 6 has a flexural strength of 83.19 MPa and a density of 2.35 g / cm 3 .
[0107] Comparative Example 7
[0108] A basalt fiber-reinforced low-expansion glass-based composite material, which is different from Example 4 in that the muffle furnace in step 5) is heated to 840° C., and the remaining steps are the same as Example 4.
[0109] The basalt fiber-reinforced glass-based composite material obtained in this comparative example 7 has a flexural strength of 75.35 MPa and a density of 2.34 g / cm 3 .
[0110] The above are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A basalt fiber toughened low expansion glass-based composite material, characterized in that: The invention comprises the following components in percentage by weight: 30wt%-48wt% of beta-eucryptite, 0.2wt%-6wt% of basalt fiber and 51.5wt%-67.5wt% of high borosilicate glass powder.
2. The basalt fiber-reinforced low-expansion glass-based composite material according to claim 1, characterized in that: The diameter of the basalt fiber is 5-10 μm; The aspect ratio of the basalt fiber is 15-30.
3. The basalt fiber-reinforced low-expansion glass-based composite material according to claim 1, characterized in that: The high borosilicate glass powder includes SiO2, B2O3, Al2O3, Na2O, and ZnO; The particle size of the high borosilicate glass powder is 0.2-0.5 μm.
4. The basalt fiber-reinforced low-expansion glass-based composite material according to claim 1, characterized in that: The particle size of the β-eucryptite is 0.2-0.9 μm.
5. A method for preparing a basalt fiber-reinforced low-expansion glass-based composite material, characterized in that: The glass-based composite material toughened by basalt fiber as claimed in any one of claims 1 to 4 comprises the following preparation steps: S1. Take β-eucryptite, basalt fiber and high borosilicate glass powder according to the proportions for use; S2, taking tetraethyl orthosilicate and aluminum isopropoxide respectively, mixing them to prepare an alkaline aqueous solution, placing the basalt fiber in step S1 in the alkaline aqueous solution, heating and stirring, and preparing a basalt fiber premix; S3, adding the β-eucryptite and high borosilicate glass powder in step S1 and the basalt premix prepared in step S2 to a ball mill, adding zirconium oxide balls to the ball mill, setting the speed and time of the ball mill to obtain a uniform slurry, and ultrasonically degassing the uniform slurry to obtain a ternary composite slurry; S4, placing the ternary composite slurry obtained in step S3 in a prefabricated dry gypsum mold, leaving it to solidify for 10-16 hours, and then demolding it to obtain a composite green body; S5, drying the composite material green body obtained in step S4 to obtain a composite material green body; S6, sintering the composite material blank obtained in step S5 to obtain a basalt fiber-reinforced glass-based composite material.
6. The method for preparing a basalt fiber-reinforced low-expansion glass-based composite material according to claim 5, characterized in that: In step S2, the concentration of tetraethyl orthosilicate is 2wt%-10wt%, and the concentration of aluminum isopropoxide is 1wt%-5wt%; The heating temperature in step S2 is 30-55° C., and the stirring is performed for 30-60 minutes by means of magnetic stirring.
7. The method for preparing a basalt fiber-reinforced low-expansion glass-based composite material according to claim 5, characterized in that: In step S3, the ratio of the zirconia balls to the material in the ball mill is 2:1, the diameter of the zirconia balls is 3-5 mm, the rotation speed of the ball mill is 150-250 rpm, and the time is 1-2 h.
8. The method for preparing a basalt fiber-reinforced low-expansion glass-based composite material according to claim 5, characterized in that: The solid content of the uniform slurry in step S3 is 50-62.5%; The uniform slurry in step S3 is subjected to ultrasonic defoaming under vacuum conditions, with a vacuum degree of -0.01 to -0.03 MPa, an ultrasonic power of 40 to 50 W, and an ultrasonic time of 10 to 15 min.
9. The method for preparing a basalt fiber-reinforced low-expansion glass-based composite material according to claim 5, characterized in that: The drying process in step S5 includes: drying the composite green body at a temperature of 21-25° C. and a humidity of 60-80% for 1-3 days, and then drying at a temperature of 50-60° C. for 12-36 hours.
10. The method for preparing a basalt fiber-reinforced low-expansion glass-based composite material according to claim 5, characterized in that: The sintering process in step S6 includes: placing the composite body in a muffle furnace, applying a pressure of 15-50 MPa to the sample by mechanical pressure, setting the temperature of the muffle furnace to 860-900° C., the vacuum degree to -0.8 to -0.9 MPa, sintering for 3-7 hours, cooling to 560-580° C., keeping the temperature for 1-2 hours, and then naturally cooling to 21-26° C.; The heating rate of the muffle furnace is 3-6℃ / min; The cooling rate of the muffle furnace is 3-8℃ / min.